Autism Learning Mobile Application - Satiakumar, Mohishaa; Mohd Rashid, Nurul Ain Binti; Hut, Norliyana Binti; Mohd Nasir, Fawwaz (Multidisciplinary Applied Research and Innovation, 2022)
Autism is a subset of Autism Spectrum Disorder (ASD), which may be categorised as developmental problems or intellectual impairments characterised by a lack of mutual social engagement, social expression, and social inventiveness. This project aims to develop a smartphone learning application for autism kids aged seven to eight because they are about to venture into much more self-care skills in their daily life. The method used for development is the Iterative Waterfall Model, which is an extension of the traditional Waterfall model. The ability to swiftly adjust to the changing needs of both the job and the demand of the clients is the most significant benefit of the iterative model. The Abstract for this project will be focussed on the development and testing of AutiVid. Testing was carried out with Autistic participants to get more feedback to improve the mobile application. The development operation will be done by extending the modules and the activities. Upcoming final year students can extend this application by providing more languages such as Tamil and Mandrin so that the application will be more useful for the autism kids.